Intussusception: Diagnosis and Management According to the Competence of Primary Service Doctors - Nazzirah Al Ammari; Harsali Lampus; Andreas Kurniawan (e-CliniC, 2022)
Abstract: Intussusception is defined as the invagination of a bowel segment into another. Intussusception can occur at any age but it is most common in children aged three months to two years. In children, the cause of intussusception is idio-pathic and is assumed to be associated with uncoordinated intestinal peristalsis or lymphoid hyperplasia, which may be due to gastrointestinal infection. Clinical findings include intermittent abdominal pain, vomiting, and red currant jelly stools. The diagnosis of intussusception is confirmed by using contrast enema, ultrasound, and CT-Scan. Improving condition must be done before performing a surgery. In conclusion, intussusception has a good prognosis with early diagnosis and treat-ment. Surgery is an option if the intussusception is followed with complication or if the enema reduction fails.Keywords: intussusception; invaginationAbstract: Intussusception is defined as the invagination of a bowel segment into another. Intussusception can occur at any age but it is most common in children aged three months to two years. In children, the cause of intussusception is idiopathic and is assumed to be associated with uncoordinated intestinal peristalsis or lymphoid hyperplasia, which may be due to gastrointestinal infection. Clinical findings include intermittent abdominal pain, vomiting, and red currant jelly stools. The diagnosis of intussusception is confirmed by using contrast enema, ultrasound, and CT-Scan. Improving condition must be done before performing a surgery. In conclusion, intussusception has a good prognosis with early diagnosis and treatment. Surgery is an option if the intussusception is followed with complication or if the enema reduction fails.Keywords: intussusception; invagination